Ambient PM2.5 exposure and hospital cost and length of hospital stay for respiratory diseases in 11 cities in Shanxi Province, China. Issue 8 (4th June 2021) - Cao, Dawei; Li, Dongyan; Wu, Yinglin; Qian, Zhengmin (Min); Liu, Yi; Liu, Qiyong; Sun, Jimin; Guo, Yuming; Zhang, Shiyu; Jiao, Guangyuan; Yang, Xiaoran; Wang, Chongjian; et al.
Abstract : Background: Few studies have examined the effects of ambient particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5 ) on hospital cost and length of hospital stay for respiratory diseases in China. Methods: We estimated ambient air pollution exposure for respiratory cases through inverse distance-weighted averages of air monitoring stations based on their residential address and averaged at the city level. We used generalised additive models to quantify city-specific associations in 11 cities in Shanxi and a meta-analysis to estimate the overall effects. We further estimated respiratory burden attributable to PM2.5 using the standards of WHO (25 µg/m 3 ) and China (75 µg/m 3 ) as reference. Results: Each 10 µg/m 3 increase in lag03 PM2.5 corresponded to 0.53% (95% CI: 0.33% to 0.73%) increase in respiratory hospitalisation, an increment of 3.75 thousand RMB (95% CI: 1.84 to 5.670) in hospital cost and 4.13 days (95% CI: 2.51 to 5.75) in length of hospital stay. About 9.7 thousand respiratory hospitalisations, 132 million RMB in hospital cost and 145 thousand days of hospital stay could be attributable to PM2.5 exposures using WHO's guideline as reference. We estimated that 193 RMB (95% CI: 95 to 292) in hospital cost and 0.21 days (95% CI: 0.13 to 0.30) in hospital stay could be potentially avoidable for an average respiratory case. Conclusion: Significant respiratory burden could be attributable to PM2.5 exposures in Shanxi Province, China. The results need to be factored into impact assessment of air pollution policies to provide a more complete indication of the burden addressed by the policies.